Amplitude and phase response of DAS receivers - Bona, A.; Dean, T.; Correa, J.; Pevzner, R.; Tertyshnikov, Konstantin; Van Zaanen, L. (2017)
The emergence of distributed acoustic sensing (DAS) as a method for acquiring seismic data has inevitably resulted in comparisons between DAS and geophone data. Herein we present and analyse the differences between the amplitude and phase spectra of the two types of datasets in terms of the pulse and gauge lengths. We have shown and demonstrated using both synthetic and field data examples that the effect of the lengths on phase is considerable, leading to changes of the shape of the wavelet and, possibly more importantly, the arrival time. The presented process can easily correct the phase of DAS data, and we expect this to become a standard part of DAS data processing. We have also quantified for what wavelengths the commonly used approximation of a DAS receiver directivity pattern by cosine squared is valid - the wavelengths should be at lest four times longer that the gauge length and the pulse length.